Cost-effectiveness of stem cell therapy versus standard of care for acute and subacute ischemic stroke - Soichiro Takamiya; Yasuhiro Morii; Toshiya Osanai; Kazuki Ohashi; Katsuhiko Ogasawara; Kiyohiro Houkin; Miki Fujimura (PLoS ONE, 2026)
A recent meta-analysis demonstrated the efficacy of stem cell therapy for ischemic stroke; however, its cost-effectiveness has not yet been sufficiently explored. Building on the clinical data from that meta-analysis, we aimed to evaluate the cost-effectiveness of the administration of mesenchymal stem cells for acute and subacute ischemic stroke compared with the standard of care. A cost-utility analysis was performed via simulation by using a Markov model. The participants were patients treated for acute or subacute ischemic stroke in hospitals in Japan. Stem cell therapy plus the standard of care (the stem cell group) was compared with the standard of care alone (the control group). The time horizon was 10 years. The primary outcome was the cost of stem cell therapy when the incremental cost-effectiveness ratio, calculated based on costs and quality-adjusted life years for both groups, was 5 million yen/quality-adjusted life year, the reference value in the cost-effectiveness evaluation in Japan. Efficacy data are obtained from the meta-analysis. Base-case analysis was performed using the most plausible or average values for all input parameters. Scenario and sensitivity analyses were also conducted. In the base case, the stem cell therapy cost when the incremental cost-effectiveness ratio was 5 million yen/quality-adjusted life year was $,3,746 from the public health payer’s perspective and $5,157 from the public healthcare and long-term care payer’s perspective. The scenario and sensitivity analyses supported the cost-effectiveness of stem cell therapy for acute and subacute ischemic stroke. This study provides threshold costs of stem cell therapy at which it becomes cost-effective for acute and subacute ischemic stroke. These results may support rational pricing strategies for stem cell therapy and facilitate its seamless integration into clinical practice.